Review of Islamic Law Compilation on the Obligation to Provide a Buffalo Dowry in Marriage (A Case Study in Sidigede Village, Welahan District, Jepara Regency) - Muhammad Hilalut Tamami; Muhammad Taufiq Zam Zami (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
The giving of a buffalo dowry or Prasah is a tradition in the customary marriage of Sidigede Village, Welahan District, Jepara Regency, in which a male buffalo is given by the prospective groom to the prospective bride. The buffalo Prasah has become an identity or characteristic that distinguishes Sidigede Village from other villages. The obligation to give a buffalo dowry is carried out when parents marry off their only son to a local village girl. This study was conducted to determine the application of the dowry obligation in traditional marriages in Sidigede Village, Welahan District, Jepara Regency, and to determine the review of the Compilation of Islamic Law regarding the obligation to give a buffalo dowry in Sidigede Village, Welahan District, Jepara Regency. In this study, the author used field research and an empirical juridical approach. The data collection techniques used were interviews, observation and documentation. The results of this study show that the community of Sidigede Village, Welahan District, Jepara Regency has a very unique tradition in traditional marriage, where in this traditional marriage, the prospective groom gives a dowry of a super-sized male buffalo worth 50 million rupiah or more, which is termed prasah. The obligation to provide a buffalo prasah is carried out when parents marry off their only son to a local village girl. Therefore, even if the groom's family is economically disadvantaged, they will still try to fulfil this obligation. The Compilation of Islamic Law explains the procedures and determination of dowry payments, as contained in Articles 30, 31, 32, 33 paragraphs (1) and (2), 34 paragraphs (1) and (2), and 38 paragraphs (1) and (2). These articles are broadly in line with the practice of giving dowry carried out by the Sidigede community, but the practice of requiring a buffalo is not in line with Article 31 of the KHI, which regulates the simplicity and ease of dowry.